Integrating Digital Technology in Christian Religious Education: A Theological Framework for Faith Formation in the Digital Age - Nella Mariana Panjaitan (Indonesian Journal of Christian Education and Theology, 2026)
The rapid development of digital technology has transformed education, including Christian Religious Education (CRE). However, technology integration in CRE often remains technical and lacks a clear theological foundation for faith formation. This study aims to analyze the integration of digital technology in CRE and develop a conceptual framework relevant to learning in the digital age. This study employs a qualitative approach using a critical literature review method through analysis and synthesis of relevant scholarly sources. The findings show that digital technology can enhance interactivity, accessibility, and creativity in learning, yet it also presents challenges such as distraction and superficial learning. As its main contribution, this study proposes a Faith-Centered Digital Learning Framework integrating digital tools, pedagogical design, and spiritual formation. The framework positions faith as the center of learning, ensuring technology supports spiritual transformation rather than merely information delivery.